Nature Loss and Climate Change: The Twin-Crises Multiplier - Stefano Giglio; Theresa Kuchler; Johannes Stroebel; Olivier Wang (CESifo GmbH, 2025)
We study the economic effects of the interaction of nature loss and climate change in a model that incorporates important aspects of both processes. We capture the distinct ways in which they affect economic activity—with nature constituting a key factor of production and climate change destroying parts of output—but also the ways in which they interact: climate change causes nature loss, and nature provides both a carbon sink and adaptation tools to reduce climate damages. Our analysis of these feedback loops reveals a novel amplification channel—the Twin-Crises Multiplier—that systematically affects optimal climate and nature conservation policies.
Keywords: 330; climate change; biodiversity loss